Becoming and Belonging in Gay Men's Life Stories: A Case Study of a Voluntaristic Model of Identity. (December 2014) - Rowe, Matthew
This article contributes to sociological studies of identity by shedding light on concrete social identification practices and placing these practices in cultural context. Gay men's autobiographical accounts, gathered in 28 in-depth interviews, show consistent use of a long-held feature of American culture: a voluntaristic trope of personal striving through social attachments. Citing examples from stories about friendship, love, role models, city life, identity politics, and religion, the analysis shows how gay men frame their life stories using a voluntaristic model of identity. The study also provides evidence of change over time in the practices through which gay men construct social identities. Younger men report greater ease in finding gay role models, especially in professional settings, than do older men. Their accounts also support the notion that a therapeutic ethos is becoming ever more pervasive in American life.